Genome-Wide Characterization of DNase I-Hypersensitive Sites and Cold Response Regulatory Landscapes in Grasses. Issue 8 (29th May 2020) - Han, Jinlei; Wang, Pengxi; Wang, Qiongli; Lin, Qingfang; Chen, Zhiyong; Yu, Guangrun; Miao, Chenyong; Dao, Yihang; Wu, Ruoxi; Schnable, James C.; Tang, Haibao; Wang, Kai
Abstract : Compiling of genome-wide DNase I-hypersensitive site maps from root, stem, and leaf tissues of multiple grasses reveals regulatory DNA landscapes and the core cold-stress response regulatory network. Abstract: Deep sequencing of DNase-I treated chromatin (DNase-seq) can be used to identify DNase I-hypersensitive sites (DHSs) and facilitates genome-scale mining of de novo cis -regulatory DNA elements. Here, we adapted DNase-seq to generate genome-wide maps of DHSs using control and cold-treated leaf, stem, and root tissues of three widely studied grass species: Brachypodium distachyon, foxtail millet ( Setaria italica ), and sorghum ( Sorghum bicolor ). Functional validation demonstrated that 12 of 15 DHSs drove reporter gene expression in transiently transgenic B. distachyon protoplasts. DHSs under both normal and cold treatment substantially differed among tissues and species. Intriguingly, the putative DHS-derived transcription factors (TFs) are largely colocated among tissues and species and include 17 ubiquitous motifs covering all grass taxa and all tissues examined in this study. This feature allowed us to reconstruct a regulatory network that responds to cold stress. Ethylene-responsive TFs SHINE3, ERF2, and ERF9 occurred frequently in cold feedback loops in the tissues examined, pointing to their possible roles in the regulatory network. Overall, we provide experimental annotation of 322, 713 DHSs and 93 derived cold-response TF binding motifs in multiple grasses, which could serve as a valuable resource for elucidating the transcriptional networks that function in the cold-stress response and other physiological processes.